2019
DOI: 10.17221/565/2019-pse
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between physiological tests and field emergence in treated corn seeds

Abstract: The objective of this work was to evaluate the degree of linear association between field emergence with the results of germination and vigor of corn seeds belonging to different initial vigor and submitted to agrochemical treatment. Following seed treatments with (i) carbendazim/thiram + imidaclopride/tiodicarbe; (ii) piraclostrobine, methyl tiophanate and fipronil; (iii) methyl tiophanate/fluazinam + bifentrine/imidaclopride; and (iv) metalaxyl-m/fludioxonil + thiamethoxam, seeds belonging to four different … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
5
0
4

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 17 publications
1
5
0
4
Order By: Relevance
“…Our data on Pearson correlation corroborate Pereira et al (2019), who also reported that grain treatment interfered in the relationship between emergence in the sand with the other tests physiological tests in maize. Indeed, based on the correlation values of Table 4, the most suitable test for predicting wheat seedling emergence in the sand varied with chemical treatment.…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…Our data on Pearson correlation corroborate Pereira et al (2019), who also reported that grain treatment interfered in the relationship between emergence in the sand with the other tests physiological tests in maize. Indeed, based on the correlation values of Table 4, the most suitable test for predicting wheat seedling emergence in the sand varied with chemical treatment.…”
Section: Resultssupporting
confidence: 91%
“…The evaluation of the physiological potential of the grains was carried out by means of the tests of germination (MAPA 2009), first germination count (MAPA 2009), accelerated aging (ISTA 2017), electrical conductivity (AOSA 2002), modified cold test (Pereira et al 2019), emergence in the sand test (Pereira et al 2019), dry seedling mass (Nakagawa 1999), as well as seedling growth tests (shoot length, root length, and total seedling length), according to the method described by Abati et al (2014).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Esquema detalhado dos tratamentos industriais de sementes de soja com seus respectivos períodos de armazenamento. Após o tratamento das sementes, a qualidade fisiológica das sementes foi avaliada por meio dos seguintes testes: teste de germinação (De Sementes, 2009), teste primeira contagem da germinação (De Sementes, 2009), comprimento da parte aérea (Abati et al, 2014), comprimento da planta inteira (Abati et al, 2014), comprimento de raiz (Abati et al, 2014), índice de velocidade de emergência (Nakagawa, 1994), emergência final (Pereira, et al 2019), teste de envelhecimento acelerado (Marcos Filho 1999).…”
Section: Materiais E Métodosunclassified
“…With regard to electrical conductivity or potassium leakage, Miguel and Marcos Filho (2002), Pereira et al (2019), Sharma et al (2011), and Zucareli et al (2013), among other authors, report high degrees of correlation between those tests, when applied to seeds, and the subsequent performance observed at field condition.…”
mentioning
confidence: 96%